2019
DOI: 10.1021/acscatal.9b01039
|View full text |Cite
|
Sign up to set email alerts
|

3-Acetoxyquinuclidine as Catalyst in Electron Donor–Acceptor Complex-Mediated Reactions Triggered by Visible Light

Abstract: Only substoichometric amounts (10 to 25 mol%) were needed to trigger the desired reaction. The outcome could be tuned by selecting the nature of the formed radical to perform amino-and hydro-decarboxylation, dimerization, and cyclization reactions. Importantly, no external additives were needed in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 39 publications
1
80
0
Order By: Relevance
“…Five-membered nitrogen-, sulfur-and oxygenbased heteroarenes (1-5) were all well tolerated. Electron-rich arenes also reacted well under our reaction conditions (6)(7)(8)(9). Moreover, the reaction with 1,3,5-trimethoxybenzene (6) could be performed at 1 mmol scale without any loss in reactivity.…”
Section: Scheme 1 Examples Of Catalytic Charge-transfer Complexesmentioning
confidence: 61%
“…Five-membered nitrogen-, sulfur-and oxygenbased heteroarenes (1-5) were all well tolerated. Electron-rich arenes also reacted well under our reaction conditions (6)(7)(8)(9). Moreover, the reaction with 1,3,5-trimethoxybenzene (6) could be performed at 1 mmol scale without any loss in reactivity.…”
Section: Scheme 1 Examples Of Catalytic Charge-transfer Complexesmentioning
confidence: 61%
“…In 2019, Bosque and Bach [ 41 ] reported that 3-acetoxyquinuclidine (q-OAc) could be utilized as an electron-donor catalyst to form an EDA complex with electron acceptor 158 , and then a molecule of carbon dioxide was removed under 455 nm light irradiation, giving decarboxylation product 159 ( Scheme 55 ). It was found that many ester groups can be activated by the structural motif of tetrachlorophthalimide in 158 .…”
Section: Reviewmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] In a few cases, a quinuclidinium radical cation also works as an oxidant that reacts with nucleophilic radicals or transient-metal intermediate through single electron transfer Please do not adjust margins Please do not adjust margins (SET). 29,30 However, as an electrophilic species, the quinuclidinium radical cation adds to olefin has not yet been revealed. We suspect that the obtained β-quinuclidinium radical species, structurally similar to β-quinuclidinium carbanion zwitterions, may provide an opportunity to achieve the MBH reaction for non-electron-deficient olefins (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%